Lung and Gut Microbiota as Potential Hidden Driver of Immunotherapy Efficacy in Lung Cancer - Carmine Carbone; Geny Piro; Vincenzo Di Noia; Ettore D’Argento; Emanuele Vita; Miriam Grazia Ferrara; Sara Pilotto; Michele Milella; Giovanni Cammarota; Antonio Gasbarrini; Giampaolo Tortora; Emilio Bria (Mediators of Inflammation)
Lung cancer is one of the deadliest and most common malignancies in the world, representing one of the greatest challenges in cancer treatment. Immunotherapy is rapidly changing standard treatment schedule and outcomes for patients with advanced malignancies. However, several ongoing studies are still attempting to elucidate the biomarkers that could predict treatment response as well as the new strategies to improve antitumor immune system response ameliorating immunotherapy efficacy. The complex of bacteria, fungi, and other microorganisms, termed microbiota, that live on the epithelial barriers of the host, are involved in the initiation, progression, and dissemination of cancer. The functional role of microbiota has attracted an accumulating attention recently. Indeed, it has been demonstrated that commensal microorganisms are required for the maturation, education, and function of the immune system regulating the efficacy of immunotherapy in the anticancer response. In this review, we discuss some of the major findings depicting bacteria as crucial gatekeeper for the immune response against tumor and their role as driver of immunotherapy efficacy in lung cancer with a special focus on the distinctive role of gut and lung microbiota in the efficacy of immunotherapy treatment.